The Impact of Information Technology Sophistication, Management Participation, and Accounting Information Systems on Employee Performance - Nasution, Hidayat (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2024)
This study investigates the impact of information technology sophistication, management participation, and accounting information systems on employee performance at PT Bank in Medan. Utilizing a quantitative approach, the research focuses on theoretical testing by quantifying research variables and analyzing the data with statistical methods. Data analysis is conducted using SPSS version 20, which includes validity, reliability, normality, multicollinearity, heteroscedasticity, t-tests, F-tests, and R² tests. The findings reveal that information technology sophistication does not significantly influence employee performance at PT Bank in Medan. Similarly, management participation does not have a substantial effect on employee performance. However, accounting information systems do significantly impact employee performance. The results show an R Square value of 20.5%, suggesting that 20.5% of the variance in employee performance can be attributed to information technology sophistication, management participation, and accounting information systems, while the remaining 69.5% is due to other factors not included in this study.